Estrutura morfológica das formas futuras nas cantigas de Santa Maria - Borges, Poliana Rossi [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Esta tese tem por objetivo o estudo da estrutura morfofonológica das formas verbais futuras do Português Arcaico (PA), no período conhecido por trovadoresco (fins do século XII até meados do século XIV), determinando se essas formas podem ser consideradas simples (uma única palavra fonológica) ou compostas ou perifrásticas (duas palavras fonológicas). Em outras palavras, objetiva-se determinar se, na época em questão, essas formas eram analíticas (formadas pelo infinitivo do verbo principal + verbo aver conjugado no presente do indicativo, no futuro do presente, ou pelo infinitivo do verbo principal + verbo aver/ir, no pretérito imperfeito do indicativo, no futuro do pretérito) ou sintéticas (cuja estrutura é radical + vogal temática + desinência modo-temporal + desinência número-pessoal). O corpus é composto das 420 Cantigas de Santa Maria de Afonso X, tomadas a partir da edição de Mettmann (1986a, 1988, 1989). A pesquisa parte do mapeamento e do levantamento quantitativo de todas as formas futuras presentes no corpus, classificando-as quanto ao tipo (aparentemente sintéticas ou indubitavelmente analíticas), relacionando os dados mapeados com a ocorrência de clíticos e o posicionamento do acento. Os resultados obtidos são analisados a partir de critérios para distinção de formas simples e compostas colhidos em estudos anteriores (MASSINI-CAGLIARI, 1999, 2006). Foi analisado, também, o grau de gramaticalização entre o verbo principal e o auxiliar de futuro, a partir dos critérios estabelecidos por Bybee, Pagliuca e Perkins (1991). Os resultados obtidos mostram que os futuros do presente e do pretérito em PA devem ser considerados formas analíticas, constituídas do infinitivo do verbo principal mais o verbo aver conjugado no presente do indicativo, para o futuro do presente, ou do infinitivo do verbo principal seguido do verbo...

The objective of this Dissertation is to study the morphophonological structure of the future verb forms in Archaic Portuguese (AP) spoken during the so-called archaic period (late 12th C until mid 14th C), in order to establish whether these forms can be considered simple forms (a single phonological word) or compound or periphrastic (two phonological words). In other words, our objective is to determine if at the studied period these forms were analytical (formed with the infinitive of the main verb + verb aver in the present, the future indicative, or by the infinitive of the main verb + aver/ir in the past imperfect) or synthetic (base form + theme vowel + mood-time inflection + person-number inflection). The corpus is formed of 420 Cantigas de Santa Maria by Afonso X edited by Mettmann (1986a, 1988, 1989). Firstly, all future forms found in the corpus were mapped, quantified and classified as to their type (apparently synthetic or positively analytic) and these data were related with the occurrence of clitics and the stress position. The results obtained were analyzed according to criteria used in former studies (MASSINI-CAGLIARI, 1999, 2006) to distinguish simple and compound forms. The degree of grammaticalization between the main verb and the auxiliary of future was also analyzed according with criteria determined by Bybee, Pagliuca e Perkins (1991). The results show that the future indicative and conditional tenses in MP must be regarded as analytical forms, formed with whether the infinitive of the main verb and verb aver conjugated in the present indicative, in the case of future indicative, or the infinitive of the main verb and verb aver/ir conjugated in the past imperfect indicative, in the case of the conditional. The fact that the parts forming these verbs could be written separately (and even invertedly in some cases), and also that a preposition... (Complete abstract click electronic access below)
Keywords: Linguística; Lingua portuguesa - Fonologia; Lingua portuguesa - Verbos; Fonologia historica; Verb; Archaic Portuguese; Phonology